Dechloranes in lichens from the southeast Tibetan Plateau: Evidence of long-range atmospheric transport. (February 2016) - Yang, Ruiqiang; Zhang, Shujuan; Li, Xinghong; Luo, Dongxia; Jing, Chuanyong
Abstract: Dechloranes (Decs) have been recently found to occur widely in the environment even in the remote polar regions. However, the understanding of their environmental fate is rather limited. The Tibetan Plateau (TP) may be an important indicator region to study the long-range atmospheric transport and their fates of these emerging contaminants since it has very limited local sources. In the present study, Dechlorane plus (DP), Dechlorane 602 (Dec 602), Dechlorane 603 (Dec 603) and Dechlorane 604 (Dec 604) were analyzed in lichen samples from the southeast TP. The results showed that only DP and Dec 602 were detected, with a detection frequency of 89% and 100%, respectively. The average concentrations (dry weight) of ΣDP and Dec 602 were 318 pg g −1 (20–1132 pg g −1 ) and 167 pg g −1 (27–843 pg g −1 ), respectively. The DP concentration in this study was much higher than those in moss from the remote Ny-Ålesund, Arctic. The concentrations of Dec 602 were found to generally increase with increasing altitude, while DP concentrations seemingly showed an opposite altitudinal trend along the mountain slopes. No stereoselective accumulation or transformation of anti -DP and syn -DP was observed in lichens and the altitudinal behavior of the two isomers was similar. This research documented that Decs are prone to undergo LRAT and cold-trapping by the mountains in the southeast TP. Highlights: The occurrence and distribution of Dechloranes were investigated in the southeast Tibetan Plateau (TP). DP concentration in southeast TP was much higher than those in moss from the Arctic region. Different altitudinal patterns between DP and Dec 602 were identified. Decs are prone to undergo LRAT and cold-trapping by the mountains in the southeast TP.